Knowledge And Practice Regarding Oral Rehydration Therapy for Acute Diarrhea Among Mothers of Under-Five Children in An Urban Area of Puducherry, India - Saurabh, Suman; Shidam, Umakant G; Sinnakirouchenan, Manjula; Subair, Mohsina; Hou, Loo Guo; Roy, Gautam (National Journal of Community Medicine, 2014)
Background: Diarrhoea is a major cause of morbidity and mortality among under-five children. Correct knowledge regarding Oral Rehydration Therapy (ORT) helps prevent morbidity and mortality due to diarrhoea. Our objective was to assess the awareness, knowledge and practice of mothers of under-five children regarding ORT and home management of diarrhoea. Methods: A cross-sectional study was carried out during September 2012. A structured and pre-tested questionnaire was administered to all the mothers of under-five children in the study area. Results: A total of 252 children and 245 mothers were covered. Around two-thirds of mothers knew about at least one method of diarrhoea prevention. Three-fourths of mothers had heard of Oral Rehydration Solution (ORS) and knew how to prepare and administer ORS. Also, majority of mothers (82.9%) were aware about home available fluids for rehydration. Around half of the mothers who knew about ORS thought that ORS had to be discontinued if diarrhoea persisted or vomiting developed. Mothers educated only till class eight were almost twice less likely to know about ORS preparation as compared to better educated mothers (OR = 2.15, 95% CI 1.14 – 4.05, P = 0.02). No association was found between lack of knowledge regarding home available fluids with younger age, low education of mothers or low per capita income. Conclusion: Although awareness regarding ORS and home available fluids was adequate, knowledge regarding its continuation in persistent diarrhoea or vomiting was poor. Lack of education predisposed to ignorance regarding ORS preparation.